2006
DOI: 10.1680/ensu.2006.159.3.99
|View full text |Cite
|
Sign up to set email alerts
|

Banked realignment: a case study from the Humber Estuary, UK

Abstract: The majority of realignment schemes undertaken in the UK to date have involved breached realignment. However, banked realignment schemes can offer benefits in terms of creating habitats that have greater physical and biological connectivity with the wider estuary. These benefits are illustrated through a case study of a scheme at Welwick in the Humber Estuary, which is one of the few recent managed realignment schemes to involve the wholesale removal of the fronting flood embankment rather than the creation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Managed realignment is increasingly seen as an integral component of sustainable estuary management (e.g., PONTEE, HULL, and MOORE, 2006). COOPER (2003) identifies a number of circumstances in which realignment is often the preferred engineering approach.…”
Section: Discussionmentioning
confidence: 99%
“…Managed realignment is increasingly seen as an integral component of sustainable estuary management (e.g., PONTEE, HULL, and MOORE, 2006). COOPER (2003) identifies a number of circumstances in which realignment is often the preferred engineering approach.…”
Section: Discussionmentioning
confidence: 99%
“… 80 Morris 12 Pendle 61 Pontee et al . 81 Steart 52.1983 −3.0506 2014 2014; 2015; 2016 3 Burgess et al . 82 Townsend 83 Wright et al .…”
Section: Methodsmentioning
confidence: 99%
“…71 Hampshire 72 Luisetti 9 Morris 12 Pontee (in Esteves) 65 Pontee et al . 81 Creek design strategies considered: 1 = absence of initial creeks; 2 = excavation of a creek system from a natural template; 3 = excavation of artificial creeks in the absence of a natural template. …”
Section: Methodsmentioning
confidence: 99%
“…The design of the scheme made extensive use of a geographic information system (GIS) in order (a) to predict the future ratio of mudflat to saltmarsh based on the known elevation ranges of habitats 9,33 (b) that the volumes of material required for the new flood defences could be obtained from a combination of the existing defences to be dismantled and material obtained by lowering the elevations within the scheme. 28 (Fig. 2).…”
Section: Types Of Managed Realignmentmentioning
confidence: 97%
“…The main reasons for the adoption of breached realignment appear to have been the requirements to promote high accretion rates, recreate saltmarsh habitats and minimise earth works. Pontee et al 28 suggested that these schemes may have 'set the trend' for subsequent realignment schemes, with many developers and conservation bodies beginning to consider breached realignment as the preferred approach in all instances.…”
Section: Types Of Managed Realignmentmentioning
confidence: 99%